Preparation method of dustproof and easy-to-clean photovoltaic glass

By preparing a coating layer with hydrophobic properties on photovoltaic glass, the problem of photovoltaic glass being susceptible to contamination in harsh environments is solved, the photoelectric conversion efficiency, dustproof and easy-to-clean performance are improved, and the service life of photovoltaic modules is extended.

CN119330607APending Publication Date: 2025-01-21JIANGSU SIMBA NEW MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411460006.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

Photovoltaic glass is susceptible to dust and wind and sand in harsh environments, resulting in a decrease in light transmittance and affecting the photoelectric conversion efficiency of solar cells.

Method used

The use of hydrochloric acid as a catalyst, and the ethyl of silicate prepares the silicon dioxide solution for the front-wheel drive system, and is mixed with polyacryonic acid-silica composite microspheres to make a mixed soluble coating solution. Solid glass is treated, and dust -proof is easy to clean the photovoltaic glass with hydrophobic performance.

Benefits of technology

It improves the photoelectric conversion efficiency, dustproof and easy-to-clean performance of photovoltaic glass, and extends the service life of photovoltaic modules.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a preparation method of dustproof and easy-to-clean photovoltaic glass, and relates to the technical field of glass. The preparation method comprises the following steps: mixing silicon dioxide, aluminum oxide, calcium fluoride, sodium carbonate, cerium oxide and ytterbium oxide, and preparing rare earth doped silicate glass by adopting a high-temperature melting method; taking the polyacrylic acid microspheres as a template and tetraethyl silicate as a precursor, and preparing polyacrylic acid-silicon dioxide composite microspheres by adopting a template method; preparing a silicon dioxide acid solution by taking hydrochloric acid as a catalyst and tetraethyl silicate as a precursor; mixing a silicon dioxide acid solution and the polyacrylic acid-silicon dioxide composite microspheres to prepare a mixed sol coating solution; the preparation method comprises the following steps: mixing 1H, 1H, 2H, 2H-perfluorooctyltriethoxysilane with absolute ethyl alcohol to prepare a hydrophobic treatment solution; and treating the rare earth doped silicate glass with the mixed sol coating solution and the hydrophobic treatment solution in sequence by adopting a dipping-pulling method to prepare the dustproof and easy-to-clean photovoltaic glass. The dustproof and easy-to-clean photovoltaic glass prepared by the invention has high photoelectric conversion performance and dustproof and easy-to-clean performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of glass, and in particular to a method for preparing dust-proof and easy-to-clean photovoltaic glass. Background Art

[0002] Photovoltaic power generation is a power generation method that converts solar energy into electrical energy through solar cells. It is green, environmentally friendly and clean. Photovoltaic glass is an important component of solar cells. The interior of photovoltaic modules requires a certain gas environment. Photovoltaic glass, as the outer shell of photovoltaic modules, can effectively isolate the air, stabilize the internal atmosphere, and ensure the normal operation of photovoltaic modules. The solar cell chips in photovoltaic modules are very fragile and easily subject to physical damage and chemical corrosion from the outside world. Photovoltaic glass, as a protective layer, can avoid this series of problems and extend the service life of photovoltaic modules. Since photovoltaic power generation equipment is outdoors for a long time, even in harsh environments such as the Gobi Desert, it is exposed to wind, sun and rain all year round, and there is a lot of dust and sand. The glass surface is easy to get dirty, and stains are difficult to remove, which reduces the light transmittance of photovoltaic glass and affects the photoelectric conversion efficiency of solar cells. Therefore, the invention of a photovoltaic glass with dust-proof and easy-to-clean properties has broad market prospects. Summary of the invention

[0003] The purpose of the present invention is to provide a method for preparing dust-proof and easy-to-clean photovoltaic glass to solve the problems existing in the prior art.

[0004] In order to solve the above technical problems, the present invention provides the following technical solutions: A dustproof and easy-to-clean photovoltaic glass. The dustproof and easy-to-clean photovoltaic glass is prepared by using hydrochloric acid as a catalyst and tetraethyl silicate as a precursor to prepare a silicate acid solution; the silicate acid solution and polyacrylic acid-silicon dioxide composite microspheres are mixed to prepare a mixed sol coating liquid; and a rare earth-doped silicate glass is treated with the mixed sol coating liquid and a hydrophobic treatment liquid in sequence by an immersion-pulling method to prepare the dustproof and easy-to-clean photovoltaic glass.

[0005] As an optimization, the rare earth doped silicate glass is prepared by mixing silicon dioxide, aluminum oxide, calcium fluoride, sodium carbonate, cerium oxide and ytterbium oxide and then adopting a high temperature melting method.

[0006] As an optimization, the polyacrylic acid-silicon dioxide composite microspheres are prepared by a template method using polyacrylic acid microspheres as a template and tetraethyl silicate as a precursor.

[0007] As an optimization, the hydrophobic treatment liquid is prepared by mixing 1H,1H,2H,2H-perfluorooctyltriethoxysilane with anhydrous ethanol.

[0008] A method for preparing dust-proof and easy-to-clean photovoltaic glass comprises the following preparation steps: (1) Mix silicon dioxide, aluminum oxide, calcium fluoride, sodium carbonate, cerium oxide and ytterbium oxide in a mass ratio of 1:(0.33~0.35):(0.44~0.46):(0.33~0.35):(0.011~0.013):(0.044~0.046) and grind them in a ceramic grinding body for 50~60 minutes to obtain a mixed powder; pour the mixed powder into a corundum crucible, and then put the corundum crucible into a silicon-molybdenum rod electric furnace, and set the target of the silicon-molybdenum rod electric furnace. The temperature is set to 1480-1500°C, and the heating program is used to set the time to 3 hours. After heating to the target temperature, the temperature is kept for 2-3 hours to obtain a mixed glass liquid; the mixed glass liquid is poured into a preheated graphite mold, and the graphite mold is placed at 490-510°C for 2-3 hours, cooled naturally to room temperature, taken out, and polished with 400-600 mesh sandpaper for 20-30 minutes, and then polished with 6000-8000 mesh sandpaper for 30-40 minutes to obtain a rare earth doped silicate glass; (2) Under the stirring conditions of 10-30°C and 300-500 r / min, 0.03-0.05 times the mass of tetraethyl silicate was added dropwise into the mixed solution once every hour for 3 times, and the mixture was stirred for 3-4 hours. The mixture was allowed to stand for 20-24 hours, centrifuged, washed with anhydrous ethanol and deionized water for 3-5 times respectively, and dried at 50-60°C under vacuum for 8-10 hours to obtain polyacrylic acid-silica composite microspheres; (3) The polyacrylic acid-silica composite microspheres and the silica acid solution are mixed uniformly in a mass ratio of 1:(1600-2000), and ultrasonically dispersed for 10-20 minutes to prepare a mixed sol coating solution; the rare earth doped silicate glass is immersed in the mixed sol coating solution, allowed to stand for 10-12 minutes, the rare earth doped silicate glass is extracted at a speed of 2600-2900 μm / s, cured at 170-190°C for 15-25 minutes, sent into a muffle furnace, tempered at 740-760°C for 6-8 minutes, taken out, and cooled to room temperature to obtain a coated anti-reflection silicate glass; the coated anti-reflection silicate glass is immersed in a hydrophobic treatment solution, allowed to stand for 20-22 minutes, the coated anti-reflection silicate glass is extracted at a speed of 190-210 μm / s, and dried at 140-160°C for 2-3 hours to obtain a dust-proof and easy-to-clean photovoltaic glass.

[0009] As an optimization, the mixed liquid in step (2) is prepared by uniformly mixing polyacrylic acid, ammonia water and deionized water in a mass ratio of 1:(4-6):(20-30), ultrasonically dispersing for 10-12 minutes to prepare an acrylic acid solution; and at 10-30° C. and 300-500 r / min stirring conditions, the acrylic acid solution is uniformly added dropwise over 10 minutes to anhydrous ethanol with a mass 10-12 times that of the acrylic acid solution to prepare the mixed liquid.

[0010] As an optimization, the model of the polyacrylic acid is PAA2000.

[0011] As an optimization, the silica acid solution in step (3) is prepared by uniformly mixing tetraethyl silicate, polyether and isopropanol in a mass ratio of 1:(1.1-1.3):(9-11), stirring at 10-30° C. and 300-500 r / min for 10-20 min, adding hydrochloric acid in an amount of 0.2-0.3 times the mass of tetraethyl silicate and isopropanol in an amount of 8-10 times the mass of tetraethyl silicate, and continuing stirring for 10-20 min.

[0012] As an optimization, the polyether has a model of 1185 A FHF.

[0013] As an optimization, the hydrophobic treatment liquid in step (3) is prepared by uniformly mixing 1H,1H,2H,2H-perfluorooctyltriethoxysilane and anhydrous ethanol in a volume ratio of 1:(2~3).

[0014] Compared with the prior art, the beneficial effects achieved by the present invention are: When preparing the dustproof and easy-to-clean photovoltaic glass, the present invention comprises the following steps: mixing silicon dioxide, aluminum oxide, calcium fluoride, sodium carbonate, cerium oxide and ytterbium oxide, and adopting a high-temperature melting method to prepare rare earth doped silicate glass; using polyacrylic acid microspheres as a template and tetraethyl silicate as a precursor, adopting a template method to prepare polyacrylic acid-silicon dioxide composite microspheres; using hydrochloric acid as a catalyst and tetraethyl silicate as a precursor to prepare a silica acid solution; mixing the silica acid solution and the polyacrylic acid-silicon dioxide composite microspheres to prepare a mixed sol coating liquid; mixing 1H,1H,2H,2H-perfluorooctyltriethoxysilane with anhydrous ethanol to prepare a hydrophobic treatment liquid; and adopting an immersion-pulling method to sequentially treat the rare earth doped silicate glass with the mixed sol coating liquid and the hydrophobic treatment liquid to prepare the dustproof and easy-to-clean photovoltaic glass.

[0015] First, silicon dioxide, aluminum oxide, calcium fluoride, sodium carbonate, cerium oxide, and ytterbium oxide are mixed and then rare earth-doped silicate glass is prepared by a high-temperature melting method. The mismatch between the spectrum of solar cells and sunlight is one of the main reasons for the low efficiency of solar cells. This makes the solar cells utilize a relatively small part of the solar energy photons. By introducing rare earth ions, the ultraviolet light part of the sunlight is absorbed, the visible light band is emitted, the luminous intensity of the visible light part is enhanced, and the photoelectric conversion efficiency of the dust-proof and easy-to-clean photovoltaic glass is improved.

[0016] Secondly, polyacrylic acid-silica composite microspheres were prepared by a template method, mixed with acid-catalyzed sol to obtain a mixed sol coating solution, and dip-coated on the surface of rare earth-doped silicate glass. After high-temperature tempering, the polyacrylic acid template in the polyacrylic acid-silica composite microspheres was calcined at high temperature, decomposed into gas and water vapor and volatilized to form an anti-reflection film with a hollow structure. The porosity of the anti-reflection film increased, resulting in an increase in the light transmittance of the dust-proof and easy-to-clean photovoltaic glass, thereby improving the photoelectric conversion efficiency of the dust-proof and easy-to-clean photovoltaic glass.

[0017] Finally, 1H,1H,2H,2H-perfluorooctyltriethoxysilane and anhydrous ethanol are mixed to prepare a hydrophobic treatment liquid; the coated anti-reflection silicate glass is treated with the hydrophobic treatment liquid by an immersion-pulling method to obtain dust-proof and easy-to-clean photovoltaic glass, and a hydrophobic layer is formed on the dust-proof and easy-to-clean photovoltaic glass, giving the dust-proof and easy-to-clean photovoltaic glass excellent dust-proof and easy-to-clean properties. DETAILED DESCRIPTION

[0018] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention. Example

[0019] A method for preparing dust-proof and easy-to-clean photovoltaic glass, the method comprising the following preparation steps: (1) Silicon dioxide, aluminum oxide, calcium fluoride, sodium carbonate, cerium oxide, and ytterbium oxide are mixed evenly in a mass ratio of 1:0.33:0.44:0.33:0.011:0.044, and ground in a ceramic grinding body for 50 minutes to obtain a mixed powder; the mixed powder is poured into a corundum crucible, and then the corundum crucible is placed in a silicon-molybdenum rod electric furnace, the target temperature of the silicon-molybdenum rod electric furnace is set to 1480°C, and the heating program is set to take 3 hours. After heating to the target temperature, it is kept warm for 3 hours to obtain a mixed glass liquid; the mixed glass liquid is poured into a preheated graphite mold, and the graphite mold is placed at 490°C for 3 hours, cooled naturally to room temperature, taken out, and polished with 400-mesh sandpaper for 30 minutes, and then polished with 6000-mesh sandpaper for 40 minutes to obtain a rare earth-doped silicate glass; (2) Polyacrylic acid, ammonia water and deionized water were mixed in a mass ratio of 1:4:20, and ultrasonically dispersed for 12 minutes to prepare an acrylic acid solution; under stirring conditions of 10°C and 300 r / min, the acrylic acid solution was uniformly added dropwise to anhydrous ethanol with a mass 10 times that of the acrylic acid solution within 10 minutes to prepare a mixed solution; under stirring conditions of 10°C and 300 r / min, tetraethyl silicate with a mass 0.03 times that of the mixed solution was added dropwise to the mixed solution once every hour for 3 times, and the reaction was continued by stirring for 4 hours. The mixture was allowed to stand for 20 hours, and then centrifuged and washed with anhydrous ethanol and deionized water for 3 times each. The mixture was dried at 50°C for 10 hours under vacuum conditions to prepare polyacrylic acid-silica composite microspheres; (3) Tetraethyl silicate, polyether and isopropanol were mixed at a mass ratio of 1:1.1:9, stirred at 10°C and 300 r / min for 20 min, hydrochloric acid (0.2 times the mass of tetraethyl silicate) and isopropanol (8 times the mass of tetraethyl silicate) were added, and stirring was continued for 20 min to prepare a silicate acid solution; polyacrylic acid-silicon dioxide composite microspheres and silicate acid solution were mixed at a mass ratio of 1:1600, ultrasonically dispersed for 10 min, and prepared into a mixed sol coating solution; rare earth doped silicate glass was immersed in the mixed sol coating solution, allowed to stand for 10 min, and heated for 26 00μm / s, extract the rare earth doped silicate glass, solidify it at 170℃ for 25min, put it into a muffle furnace, temper it at 740℃ for 8min, take it out, and cool it to room temperature to obtain coated anti-reflection silicate glass; 1H,1H,2H,2H-perfluorooctyltriethoxysilane and anhydrous ethanol are mixed evenly in a volume ratio of 1:2 to prepare a hydrophobic treatment liquid; immerse the coated anti-reflection silicate glass in the hydrophobic treatment liquid, let it stand for 20min, extract the coated anti-reflection silicate glass at a speed of 190μm / s, and dry it at 140℃ for 3h to obtain dust-proof and easy-to-clean photovoltaic glass. Example

[0020] A method for preparing dust-proof and easy-to-clean photovoltaic glass, the method comprising the following preparation steps: (1) Silicon dioxide, aluminum oxide, calcium fluoride, sodium carbonate, cerium oxide, and ytterbium oxide were mixed evenly in a mass ratio of 1:0.34:0.45:0.34:0.012:0.045, and ground in a ceramic grinding body for 55 minutes to obtain a mixed powder; the mixed powder was poured into a corundum crucible, and then the corundum crucible was placed in a silicon-molybdenum rod electric furnace, and the target temperature of the silicon-molybdenum rod electric furnace was set to 1490°C, and the heating program was set to take 3 hours. After heating to the target temperature, it was kept warm for 2.5 hours to obtain a mixed glass liquid; the mixed glass liquid was poured into a preheated graphite mold, and the graphite mold was kept warm at 500°C for 2.5 hours, cooled naturally to room temperature, taken out, and polished with 500-mesh sandpaper for 25 minutes, and then polished with 7000-mesh sandpaper for 35 minutes to obtain a rare earth-doped silicate glass; (2) Polyacrylic acid, ammonia water and deionized water were mixed in a mass ratio of 1:5:25, and ultrasonically dispersed for 11 minutes to prepare an acrylic acid solution; under stirring conditions of 20°C and 400 r / min, the acrylic acid solution was uniformly added dropwise to anhydrous ethanol with a mass that was 11 times the mass of the acrylic acid solution within 10 minutes to prepare a mixed solution; under stirring conditions of 20°C and 400 r / min, tetraethyl silicate with a mass that was 0.04 times the mass of the mixed solution was added dropwise to the mixed solution once every hour for 3 times, and the reaction was continued with stirring for 3.5 hours. The mixture was allowed to stand for 22 hours, and centrifuged, washed with anhydrous ethanol and deionized water for 4 times each, and dried at 55 for 9 hours under vacuum conditions to obtain polyacrylic acid-silica composite microspheres; (3) Tetraethyl silicate, polyether and isopropanol were mixed at a mass ratio of 1:1.2:10, stirred at 20°C and 400 r / min for 15 min, hydrochloric acid (0.25 times the mass of tetraethyl silicate) and isopropanol (9 times the mass of tetraethyl silicate) were added, and stirring was continued for 15 min to prepare a silicate acid solution; polyacrylic acid-silicon dioxide composite microspheres and silicate acid solution were mixed at a mass ratio of 1:1800) and ultrasonically dispersed for 15 min to prepare a mixed sol coating solution; rare earth-doped silicate glass was immersed in the mixed sol coating solution, allowed to stand for 11 min, and heated at 27 The rare earth-doped silicate glass was extracted at a speed of 50 μm / s, cured at 180°C for 20 min, sent into a muffle furnace, tempered at 750°C for 7 min, taken out, and cooled to room temperature to obtain a coated anti-reflection silicate glass; 1H, 1H, 2H, 2H-perfluorooctyltriethoxysilane and anhydrous ethanol were evenly mixed at a volume ratio of 1:2.5 to prepare a hydrophobic treatment liquid; the coated anti-reflection silicate glass was immersed in the hydrophobic treatment liquid, allowed to stand for 21 min, the coated anti-reflection silicate glass was extracted at a speed of 200 μm / s, and dried at 150°C for 2.5 h to obtain a dust-proof and easy-to-clean photovoltaic glass. Example

[0021] A method for preparing dust-proof and easy-to-clean photovoltaic glass, the method comprising the following preparation steps: (1) Silicon dioxide, aluminum oxide, calcium fluoride, sodium carbonate, cerium oxide, and ytterbium oxide are mixed evenly in a mass ratio of 1:0.35:0.46:0.35:0.013:0.046, and ground in a ceramic grinding body for 60 minutes to obtain a mixed powder; the mixed powder is poured into a corundum crucible, and then the corundum crucible is placed in a silicon-molybdenum rod electric furnace, the target temperature of the silicon-molybdenum rod electric furnace is set to 1500°C, and the heating program is set to take 3 hours. After heating to the target temperature, it is kept warm for 2 hours to obtain a mixed glass liquid; the mixed glass liquid is poured into a preheated graphite mold, the graphite mold is placed at 510°C and kept warm for 2 hours, and naturally cooled to room temperature, taken out, and polished with 600-mesh sandpaper for 20 minutes, and then polished with 8000-mesh sandpaper for 30 minutes to obtain a rare earth-doped silicate glass; (2) Polyacrylic acid, ammonia water and deionized water were mixed in a mass ratio of 1:6:30, and ultrasonically dispersed for 12 minutes to prepare an acrylic acid solution; under stirring conditions of 30°C and 500 r / min, the acrylic acid solution was uniformly added dropwise to anhydrous ethanol with a mass 12 times that of the acrylic acid solution within 10 minutes to prepare a mixed solution; under stirring conditions of 30°C and 500 r / min, tetraethyl silicate with a mass 0.05 times that of the mixed solution was added dropwise to the mixed solution once every hour for 3 times, and the mixture was stirred and reacted for 3 hours. The mixture was allowed to stand for 24 hours, centrifuged, washed with anhydrous ethanol and deionized water for 5 times each, and dried at 60°C under vacuum conditions for 8 hours to prepare polyacrylic acid-silica composite microspheres; (3) Tetraethyl silicate, polyether and isopropanol were mixed at a mass ratio of 1:1.3:11, stirred at 30°C and 500 r / min for 10 min, hydrochloric acid (0.3 times the mass of tetraethyl silicate) and isopropanol (10 times the mass of tetraethyl silicate) were added, and stirring was continued for 10 min to prepare a silicate acid solution; polyacrylic acid-silicon dioxide composite microspheres and silicate acid solution were mixed at a mass ratio of 1:2000, ultrasonically dispersed for 20 min, and prepared into a mixed sol coating solution; rare earth doped silicate glass was immersed in the mixed sol coating solution, allowed to stand for 12 min, and then heated to 200 °C for 12 min. The rare earth-doped silicate glass was extracted at a speed of 900 μm / s, cured at 190°C for 15 min, sent into a muffle furnace, tempered at 760°C for 6 min, taken out, and cooled to room temperature to obtain a coated anti-reflection silicate glass; 1H, 1H, 2H, 2H-perfluorooctyltriethoxysilane and anhydrous ethanol were evenly mixed at a volume ratio of 1:3 to prepare a hydrophobic treatment liquid; the coated anti-reflection silicate glass was immersed in the hydrophobic treatment liquid, allowed to stand for 22 min, the coated anti-reflection silicate glass was extracted at a speed of 210 μm / s, and dried at 160°C for 2 h to obtain a dust-proof and easy-to-clean photovoltaic glass.

[0022] Comparative Example 1 The preparation method of the dust-proof and easy-to-clean photovoltaic glass of Comparative Example 1 is different from that of Example 2 in terms of step (1) and step (3). Step (1) is modified as follows: (1) silicon dioxide, aluminum oxide, calcium fluoride and sodium carbonate are uniformly mixed in a mass ratio of 1:0.34:0.45:0.34, and ground in a ceramic grinding body for 55 minutes to obtain a mixed powder; the mixed powder is poured into a corundum crucible, and the corundum crucible is then placed in a silicon-molybdenum rod electric furnace, the target temperature of the silicon-molybdenum rod electric furnace is set to 1490°C, the heating program is set to take 3 hours, and the temperature is heated to the target temperature and then kept warm for 2.5 hours to obtain a mixed glass liquid; the mixed glass liquid is poured into a preheated graphite mold, the graphite mold is placed at 500°C and kept warm for 2.5 hours, naturally cooled to room temperature, taken out, and polished with 500-mesh sandpaper for 25 minutes, and then polished with 7000-mesh sandpaper for 35 minutes to obtain silicate glass; Step (3) is modified as follows: tetraethyl silicate, polyether and isopropanol are mixed uniformly in a mass ratio of 1:1.2:10, stirred at 20°C and 400 r / min for 15 min, hydrochloric acid (0.25 times the mass of tetraethyl silicate) and isopropanol (9 times the mass of tetraethyl silicate) are added, and stirring is continued for 15 min to prepare a silica acid solution; polyacrylic acid-silicon dioxide composite microspheres and silica acid solution are mixed uniformly in a mass ratio of 1:1800), ultrasonically dispersed for 15 min, and prepared into a mixed sol coating solution; silicate glass is immersed in the mixed sol coating solution and allowed to stand for 11 min, The silicate glass was extracted at a speed of 2750 μm / s, cured at 180°C for 20 minutes, sent into a muffle furnace, tempered at 750°C for 7 minutes, taken out, and cooled to room temperature to obtain a coated anti-reflection silicate glass; 1H, 1H, 2H, 2H-perfluorooctyl triethoxysilane and anhydrous ethanol were mixed uniformly at a volume ratio of 1:2.5 to prepare a hydrophobic treatment liquid; the coated anti-reflection silicate glass was immersed in the hydrophobic treatment liquid, allowed to stand for 21 minutes, the coated anti-reflection silicate glass was extracted at a speed of 200 μm / s, and dried at 150°C for 2.5 hours to obtain a dust-proof and easy-to-clean photovoltaic glass. The remaining steps are the same as in Example 2.

[0023] Comparative Example 2 The preparation method of the dust-proof and easy-to-clean photovoltaic glass of Comparative Example 2 is different from that of Example 2 in that step (2) is not performed, and step (3) is modified as follows: tetraethyl silicate, polyether, and isopropyl alcohol are uniformly mixed in a mass ratio of 1:1.2:10, stirred at 20°C and 400 r / min for 15 min, hydrochloric acid 0.25 times the mass of tetraethyl silicate and isopropyl alcohol 9 times the mass of tetraethyl silicate are added, and stirring is continued for 15 min to obtain a silica acid solution; the rare earth-doped silicate glass is immersed in the silica acid solution, allowed to stand for 11 min, and stirred at a speed of 2750 μm / s. The rare earth doped silicate glass was extracted at 180°C for 20 minutes, and then put into a muffle furnace, tempered at 750°C for 7 minutes, taken out, and cooled to room temperature to obtain a coated anti-reflection silicate glass; 1H, 1H, 2H, 2H-perfluorooctyl triethoxysilane and anhydrous ethanol were mixed uniformly at a volume ratio of 1:2.5 to prepare a hydrophobic treatment liquid; the coated anti-reflection silicate glass was immersed in the hydrophobic treatment liquid, and allowed to stand for 21 minutes, and the coated anti-reflection silicate glass was extracted at a speed of 200 μm / s, and dried at 150°C for 2.5 hours to obtain a dust-proof and easy-to-clean photovoltaic glass. The remaining steps are the same as those in Example 2.

[0024] Comparative Example 3 The preparation method of the dust-proof and easy-to-clean photovoltaic glass of Comparative Example 3 is different from that of Example 2 only in that step (2) is not performed, and step (3) is modified as follows: 1H, 1H, 2H, 2H-perfluorooctyl triethoxysilane and anhydrous ethanol are mixed evenly at a volume ratio of 1:2.5 to prepare a hydrophobic treatment liquid; rare earth-doped silicate glass is immersed in the hydrophobic treatment liquid, left to stand for 21 minutes, the rare earth-doped silicate glass is extracted at a speed of 200 μm / s, and dried at 150° C. for 2.5 hours to prepare a dust-proof and easy-to-clean photovoltaic glass. The remaining steps are the same as those of Example 2.

[0025] Comparative Example 4 The preparation method of the dust-proof and easy-to-clean photovoltaic glass of Comparative Example 4 is different from that of Example 2 in that step (2) is not performed, and step (3) is modified as follows: tetraethyl silicate, polyether, and isopropanol are uniformly mixed in a mass ratio of 1:1.2:10, stirred at 20°C and 400r / min for 15min, hydrochloric acid 0.25 times the mass of tetraethyl silicate and isopropanol 9 times the mass of tetraethyl silicate are added, and stirring is continued for 15min to obtain a silica acid solution; polyacrylic acid-dimethacrylate is added The silicon oxide composite microspheres and the silica acid solution are mixed evenly at a mass ratio of 1:1800, and ultrasonically dispersed for 15 minutes to prepare a mixed sol coating solution; the rare earth doped silicate glass is immersed in the mixed sol coating solution, and allowed to stand for 11 minutes, and the rare earth doped silicate glass is extracted at a speed of 2750 μm / s, and solidified at 180°C for 20 minutes, and sent to a muffle furnace, tempered at 750°C for 7 minutes, taken out, and cooled to room temperature to obtain a dust-proof and easy-to-clean photovoltaic glass. The remaining steps are the same as those in Example 2.

[0026] Test Example 1 Photoelectric conversion performance test Test method: The embodiment, comparative example and silicon crystal cell were assembled into a solar cell, and the photocurrent density-voltage characteristic curve of the solar cell was tested. The photoelectric conversion performance of the embodiment and comparative example was reflected by the magnitude of the short-circuit current. The results are shown in Table 1.

[0027] Table 1 <![CDATA[Short-circuit current (mA / cm 2 ).]]> <![CDATA[Short-circuit current (mA / cm 2 )]]> Example 1 6.5325 Comparative Example 1 6.1376 Example 2 6.5186 Comparative Example 2 6.2452 Example 3 6.4972 Comparative Example 3 6.1755 Comparative Example 4 6.4831 From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 4 in Table 1, it can be found that the dust-proof and easy-to-clean photovoltaic glass prepared by the present invention has good photoelectric conversion performance.

[0028] By comparison, the short-circuit currents of Examples 1 to 3 are greater than that of Comparative Example 1, indicating that rare earth-doped silicate glass is prepared by mixing silicon dioxide, aluminum oxide, calcium fluoride, sodium carbonate, cerium oxide and ytterbium oxide and adopting a high-temperature melting method. The mismatch between the spectrum of solar cells and sunlight is one of the main reasons for the low efficiency of solar cells, which makes the solar cell utilize a relatively small part of the solar energy photons. By introducing rare earth ions, the ultraviolet light part of the sunlight is absorbed, and the visible light band is emitted, thereby enhancing the luminous intensity of the visible light part and improving the photoelectric conversion efficiency of the dust-proof and easy-to-clean photovoltaic glass.

[0029] By comparison, the short-circuit current of Examples 1 to 3 is greater than that of Comparative Examples 2 to 3, indicating that polyacrylic acid-silica composite microspheres are prepared by a template method, mixed with an acid-catalyzed sol to obtain a mixed sol coating liquid, which is dip-coated on the surface of a rare earth-doped silicate glass and tempered at high temperature. The polyacrylic acid template in the polyacrylic acid-silica composite microspheres is calcined at high temperature, decomposed into gas and water vapor, and volatilized to form an anti-reflection film with a hollow structure. The porosity of the anti-reflection film is increased, resulting in an increase in the light transmittance of the dust-proof and easy-to-clean photovoltaic glass, thereby improving the photoelectric conversion efficiency of the dust-proof and easy-to-clean photovoltaic glass.

[0030] Test Example 2 Test of dustproof and easy-to-clean performance Test method: Test the light transmittance of the embodiment and the comparative example, and then perform a dust blowing test on the embodiment and the comparative example. The parameters of the dust blowing test are set to a quartz sand concentration of 10.6 g / m 3 , wind speed 8.9m / s, ambient temperature 23℃, installation angle 45°, after the test, wash with deionized water 3 times, test its light transmittance after drying, calculate the light transmittance change rate, and use the light transmittance change rate to characterize the dustproof and easy-to-clean performance of the embodiment and the comparative example. The results are shown in Table 2 Table 2 Light transmittance change rate (%) Light transmittance change rate (%) Example 1 3.53 Comparative Example 1 3.78 Example 2 3.41 Comparative Example 2 3.81 Example 3 3.46 Comparative Example 3 4.12 Comparative Example 4 13.67 From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 4 in Table 2, it can be found that the dust-proof and easy-to-clean photovoltaic glass prepared by the present invention has good dust-proof and easy-to-clean performance.

[0031] By comparison, the light transmittance change rate of Examples 1 to 3 is smaller than that of Comparative Example 4, indicating that 1H, 1H, 2H, 2H-perfluorooctyltriethoxysilane is mixed with anhydrous ethanol to prepare a hydrophobic treatment liquid; the coated anti-reflective silicate glass is treated with the hydrophobic treatment liquid by the immersion-pulling method to obtain dust-proof and easy-to-clean photovoltaic glass, and a hydrophobic layer is formed on the dust-proof and easy-to-clean photovoltaic glass, giving the dust-proof and easy-to-clean photovoltaic glass excellent dust-proof and easy-to-clean properties.

[0032] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.

Claims

1. A dustproof and easy-to-clean photovoltaic glass, characterized in that: The dust-proof and easy-to-clean photovoltaic glass is prepared by using hydrochloric acid as a catalyst and tetraethyl silicate as a precursor to prepare a silica acid solution; the silica acid solution and polyacrylic acid-silicon dioxide composite microspheres are mixed to prepare a mixed sol coating solution; and a rare earth-doped silicate glass is treated with the mixed sol coating solution and a hydrophobic treatment solution in sequence by an immersion-pulling method to prepare the dust-proof and easy-to-clean photovoltaic glass.

2. The dust-proof and easy-to-clean photovoltaic glass according to claim 1, characterized in that: The rare earth doped silicate glass is prepared by mixing silicon dioxide, aluminum oxide, calcium fluoride, sodium carbonate, cerium oxide and ytterbium oxide and then adopting a high temperature melting method.

3. The dustproof and easy-to-clean photovoltaic glass according to claim 1, characterized in that: The polyacrylic acid-silicon dioxide composite microspheres are prepared by using a template method with polyacrylic acid microspheres as a template and tetraethyl silicate as a precursor.

4. The dustproof and easy-to-clean photovoltaic glass according to claim 3, characterized in that: The hydrophobic treatment liquid is prepared by mixing 1H,1H,2H,2H-perfluorooctyltriethoxysilane and anhydrous ethanol.

5. A method for preparing dust-proof and easy-to-clean photovoltaic glass, characterized in that: The method comprises the following preparation steps: (1) Mix silicon dioxide, aluminum oxide, calcium fluoride, sodium carbonate, cerium oxide and ytterbium oxide in a mass ratio of 1:(0.33~0.35):(0.44~0.46):(0.33~0.35):(0.011~0.013):(0.044~0.046) and grind them in a ceramic grinding body for 50~60 minutes to obtain a mixed powder; pour the mixed powder into a corundum crucible, and then put the corundum crucible into a silicon-molybdenum rod electric furnace, and set the target of the silicon-molybdenum rod electric furnace. The temperature is set to 1480-1500°C, and the heating program is used to set the time to 3 hours. After heating to the target temperature, the temperature is kept for 2-3 hours to obtain a mixed glass liquid; the mixed glass liquid is poured into a preheated graphite mold, and the graphite mold is placed at 490-510°C for 2-3 hours, cooled naturally to room temperature, taken out, and polished with 400-600 mesh sandpaper for 20-30 minutes, and then polished with 6000-8000 mesh sandpaper for 30-40 minutes to obtain a rare earth doped silicate glass; (2) Under the stirring conditions of 10-30°C and 300-500 r / min, 0.03-0.05 times the mass of tetraethyl silicate was added dropwise into the mixed solution once every hour for 3 times, and the mixture was stirred for 3-4 hours. The mixture was allowed to stand for 20-24 hours, centrifuged, washed with anhydrous ethanol and deionized water for 3-5 times respectively, and dried at 50-60°C under vacuum for 8-10 hours to obtain polyacrylic acid-silica composite microspheres; (3) The polyacrylic acid-silica composite microspheres and the silica acid solution are mixed uniformly in a mass ratio of 1:(1600-2000), and ultrasonically dispersed for 10-20 minutes to prepare a mixed sol coating solution; the rare earth doped silicate glass is immersed in the mixed sol coating solution, allowed to stand for 10-12 minutes, the rare earth doped silicate glass is extracted at a speed of 2600-2900 μm / s, cured at 170-190°C for 15-25 minutes, sent into a muffle furnace, tempered at 740-760°C for 6-8 minutes, taken out, and cooled to room temperature to obtain a coated anti-reflection silicate glass; the coated anti-reflection silicate glass is immersed in a hydrophobic treatment solution, allowed to stand for 20-22 minutes, the coated anti-reflection silicate glass is extracted at a speed of 190-210 μm / s, and dried at 140-160°C for 2-3 hours to obtain a dust-proof and easy-to-clean photovoltaic glass.

6. The method for preparing dust-proof and easy-to-clean photovoltaic glass according to claim 5, characterized in that: The mixed solution in step (2) is prepared by uniformly mixing polyacrylic acid, ammonia water and deionized water in a mass ratio of 1:(4-6):(20-30), ultrasonically dispersing for 10-12 minutes to prepare an acrylic acid solution; and uniformly adding the acrylic acid solution to anhydrous ethanol having a mass 10-12 times that of the acrylic acid solution at 10-30° C. and 300-500 r / min stirring conditions within 10 minutes.

7. The method for preparing dust-proof and easy-to-clean photovoltaic glass according to claim 6, characterized in that: The model of the polyacrylic acid is PAA2000.

8. The method for preparing dust-proof and easy-to-clean photovoltaic glass according to claim 5, characterized in that: The silica acid solution in step (3) is prepared by uniformly mixing tetraethyl silicate, polyether and isopropanol in a mass ratio of 1:(1.1-1.3):(9-11), stirring at 10-30° C. and 300-500 r / min for 10-20 min, adding hydrochloric acid in an amount of 0.2-0.3 times the mass of tetraethyl silicate and isopropanol in an amount of 8-10 times the mass of tetraethyl silicate, and continuing stirring for 10-20 min.

9. The method for preparing dust-proof and easy-to-clean photovoltaic glass according to claim 8, characterized in that: The polyether has a model number of 1185 A FHF.

10. The method for preparing dust-proof and easy-to-clean photovoltaic glass according to claim 5, characterized in that: The hydrophobic treatment liquid in step (3) is prepared by uniformly mixing 1H,1H,2H,2H-perfluorooctyltriethoxysilane and anhydrous ethanol in a volume ratio of 1:(2-3).